Emerging technologies of algae‐based wastewater remediation for bio‐fertilizer production: a promising pathway to sustainable agriculture. Issue 3 (19th November 2020) - Zou, Yao; Zeng, Qingqing; Li, Huankai; Liu, Hui; Lu, Qian
Abstract: Soil degradation, overuse of chemical fertilizer, and biodiversity loss are serious problems challenging the sustainable development of modern agriculture. In recent years, owing to the advantages of algae biotechnology in nutrients recovery and soil improvement, the integration of algae‐based wastewater remediation and algal bio‐fertilizer production is emerging into the limelight. In this work, we emphasize on the progresses achieved in the fields of biomass production by algae cultivation in wastewater and application of algal bio‐fertilizers. Particularly, three types of algal bio‐fertilizers, including slow‐release bio‐fertilizer, nitrogen‐fixing cyanobacteria, and liquid bio‐fertilizer, widely evaluated and utilized in agriculture are introduced. To prevent the overly optimistic prediction of algal bio‐fertilizer in a real‐world application, we point out the challenges and technical defects, such as presence of new pollution factors in wastewater, high cost of algal biomass, contamination of algal biomass in wastewater, low productivity of algae and valuable components, high water consumption, and potential threats of cyanobacteria to the environment, that prevent the concept of integrating algae‐based wastewater remediation and algal bio‐fertilizer production from becoming a reality. Based on our knowledge and experience, potential solutions to the aforementioned problems are discussed in depth. It is expected that the emerging technologies of algae‐based wastewater remediation for bio‐fertilizer production will bring human beings into a new era of environmentally‐friendly, high‐yield, and resource‐recycling agriculture. © 2020 Society of Chemical Industry (SCI)